PENERAPAN PEMBERIAN MINYAK JINTAN HITAM (NIGELLA SATIVA OIL) UNTUK PENGOBATAN BIANG KERINGAT (MILIARIA) PADA BAYI DI WILAYAH PMB BRIDA KITY DINARUM S.ST - Wulan Rahmadhani; Nisfatul Annisa; Suci Amin (Jurnal Ilmu Kebidanan, 2021)
Background: Climate changes and temperature can cause prickly heat (miliaria). It is a small, itchy rash that can cause skin irritation. This can be overcome by using a medicinal plant that is black cumin oil (Nigella sativa oil). This plant is able to stop inflammation. Objective: To know the application of giving black cumin oil (Nigella sativa oil) for the treatment of prickly heat (miliaria) on babies. Method: This study is a kind of case-study research. Data were obtained from interviews, observations, and literary study. The participants were 5 babies who met the inclusion criteria. The instruments used were observation sheet, check list sheet. Result: After the application of black cumin oil (Nigella sativa oil), 3 participants had recovered from prickly heat (60%). Meanwhile, 2 participants had a change to be profunda miliaria (40%). Conclusion: The application of black cumin oil (Nigella sativa oil) is effective in treating prickly heat (miliaria) of a baby.